MAGMATIC INCLUSIONS IN THE SEARCH FOR NATURAL SILICATE-SALT MELT IMMISCIBILITY: METHODOLOGY AND EXAMPLES - Kamenetsky V.S.; Kamenetsky M.B.; Davidson P.; De Vivo B.; Naumov V.B.; Menagh T.P.; Van Achterbergh E.; Ryan C.G. (My University, 2003)
Immiscible phase separation during the cooling and crystallisation of magmas is an inherently fugitive phenomenon and melt inclusions may provide the only remaining evidence of this process. We detail those features of such inclusions that can both prove the existence of immiscible phase separation, and constrain the compositional signature of the process. To do so requires the combination of traditional methods (petrographic examination, microthermometry, etc.) with state of the art microbeam analytical techniques (laser Raman spectroscopy and proton-induced X-ray emission). Examples of inclusions in phenocrysts from barren and mineralised rocks are provided to illustrate the approach and validate the interpretations.